Efektivitas Gerakan Peduli dan Berbudaya Lingkungan Hidup pada Sekolah Menengah Atas di Kecamatan Koto Tangah - Iqbal Hadasi Putra; Adil Mubarak (ALSYS, 2025)
Environmental issues at the school level represent a strategic concern that requires serious attention, given the critical role of schools in cultivating environmentally conscious behavior from an early age. The government has addressed this issue through the Gerakan Peduli dan Berbudaya Lingkungan Hidup di Sekolah (PBLHS) program, which aims to foster an environmentally friendly culture within educational institutions. However, the program's implementation continues to face several challenges, including low participation from school communities, limited supporting facilities, and weak dissemination strategies. This study aims to analyze the effectiveness of PBLHS implementation in senior high schools in Koto Tangah District, focusing on four key indicators: target accuracy, program dissemination, goal achievement, and program monitoring. A descriptive qualitative method was employed, with data collected through observations, interviews, and document analysis, and validated through source triangulation. The results indicate that SMA Negeri 7 Padang demonstrated a high level of effectiveness across all indicators, supported by active school community engagement, adequate facilities, and an integrated environmental culture in school activities. In contrast, SMA Negeri 8 and SMA Negeri 13 Padang encountered obstacles such as low student awareness, inadequate infrastructure, and weak dissemination strategies, leading to suboptimal program execution. These findings suggest that the success of PBLHS is significantly influenced by the synergy between available resources, dissemination intensity, active participation of the school community, and consistent monitoring. The study recommends strengthening behavior-based education strategies, improving infrastructure, and ensuring consistent policy support to establish PBLHS as a sustainable school culture.